Effect of cold stress on gene expression and functional pathways in maize root system. (21st August 2019) - Ma, Yanhua; Li, Suiyan; Lin, Hong; Pan, Liyan; Yang, Guowei; Lai, Yanhua; Sun, Dequan
Abstract: This study aimed to explore the key genes and associated functions involved in the cold response of maize root under low temperature. The gene expression profiling GSE72508 was downloaded from Gene Expression Omnibus database, which included four maize varieties. Genes that were differentially expressed in maize primary root under cold conditions and normal conditions were screened in four varieties. These genes were performed functional enrichment analyses and protein–protein interaction (PPI) network establishment. Furthermore, the differentially expressed genes (DEGs) of four varieties were compared through Venn diagram to further screen key genes induced by cold stress. Totally, 116, 140, 94 and 101 DEGs were screened between cold treatment and control groups in four varieties, respectively. They were significantly enriched in functions of carbohydrate metabolic and biosynthetic processes, polysaccharide metabolic and biosynthetic processes, and glycogen metabolic and biosynthetic processes, as well as pathway of starch and sucrose metabolism, photosynthesis and ribosome. Venn diagram analysis identified two common DEGs between the four varieties: LOC100282063 and eno1 . Cold stress may influence the normal growth and development of maize through changing the metabolism and biosynthesis of sugar, as well as affecting the photosynthesis. Additionally, LOC100281989 and eno1 may be key genes involved in cold response of maize under low temperature.